FAKTOR-FAKTOR YANG MEMPENGARUHI KEKAMBUHAN PASIEN GANGGUAN JIWA: STUDI LITERATUR - letty _panjaitan16 letty_panjaitan16; Bela Purnama Dewi (Jurnal Kesehatan dan Pembangunan, 2022)
Background: Mental health is a positive attitude towards oneself, growing up having self-actualization, wholeness, self-freedom, having perceptions according to reality and skills in adapting to the environment. There are several factors that trigger the relapse of patients with mental disorders, including individual patient factors, family support factors, environmental factors, treatment factors, and health worker factors. Objective: to determine the factors that influence the recurrence of mental disorders patients. Methods: This study uses a literature review method or literature study. The type of literature review used in this study is a scoping review. The way of collecting data in this research is using literature study or literature study. The data sources in this research were obtained from google schoolar and researchgate related to the research topic, namely the factors that influence the recurrence of mental patients from 2015 to 2020. The analytical method used includes summarize. Results: there is a relationship between family support factors and the recurrence of mental disorders patients. There is a relationship between the patient's adherence to medication and the recurrence of mental disorders. There is a relationship between the support factor of the surrounding social environment on the recurrence of mental disorder patients. Suggestion: Health workers should be able to work together to reduce the factors that cause mental disorders by taking preventive measures to prevent recurrences or community-based prevention of mental disorders. In addition, health workers can also take action to the family because the family is the closest person who will take care of the client while at home.